Devires drag mediados pelas tecnologias digitais: corporalidades e identificações no interior do Rio Grande do Sul - Borges, Rafaela Oliveira (2023)
Drags are artists who give life to embodied characters for theatrical performance, as well as for fun, self-experimentation, raising self-esteem, among other motivations. Currently, men, women, transvestites, trans people and non-binary people of different sexual identities cross-dress artistically. Through performances involving fabricated corporealities, imbued with the temperaments of drag personas, the artists manifest different artistic expressions in themselves and that emanate from themselves. In view of this fact, this thesis looks at how drag performers from Santa Maria (RS/Brazil) produce corporealities and theatricalize genres to give life to artistic personas, through the different agency of identifications in a circuit onoffline practices. Based on an ethnographic investigation developed from participant observations and interviews with drag interlocutors between 2019 and 2023, and in dialogue with theories that deal with corporealities, gender performativities and identifications, I propose a reflection on how these drag experimentations take place in the digital age in which we find ourselves. Thus, I have identified that the fabrication of drag corporealities in the aforementioned circuit takes place through cyborg bricolage with make-up, clothing, wigs, smartphones, profiles, 3D filters provided by augmented reality, among countless other digital things and things. These corporealities materialize the multiple identifications of the self, in the self, through positions taken in the world, embodied in the cyborg subject's body. Furthermore, by highlighting the multiple possibilities of identifications and the production of contingent and historical differences, I identify the conditions of displacement in the world of subjects marked as non-human in this production of identifications and differences that imply including and excluding the more or less human. Finally, through the theoretical-empirical discussion, I highlight the relevance of socio-anthropological analysis that articulates human agencies and socio-cultural structures in an attempt to understand how corporealities and identifications are reconfigured in practice and which, through the arts, manifest ways of living beyond the norms that regulate bodies, genders and identifications.